Factors Influences Farmers Desire to Agricultural Land Conversion in Indonesia using Structural Equation Model Analysis - Makbul, Yogi; Ratnaningtyas, Sudrajati; ., Pradono (International Journal of Engineering and Technology, 2019)
The objective of this research is to know what factors can influence the farmers to convert his farmland for the purpose of land conversion near the trans-Java toll road. The research uses a survey on Gantar and Terisi District in Indramayu Regency, West Java Province, Indonesia. A sample of 408 farmers from ten farmer-groups has been drawn using the cluster method. The Structural Equation Method (SEM) has been used in the statistical analysis. The dependent variable is the farmerâ€™s desire to convert his farmland. The independent variables are three latent variables with 11 observed variables. The latent variables are location, agricultural environment, and lifestyle perception. The findings of this research are unique, and novel compared to other researches on agricultural land conversion. The uniqueness and novelty of this research is that first, it finds the internal factors why farmers convert their farmland. Second, this research uses the quantitative method with SEM analysis in farmland conversion. The SEM is commonly used in management research. Third, the finding of the research is essential for food security in Indonesia because the research has been conducted on Java Island. Java Island is the most strategic area for rice production in Indonesia. The island comprises only 6.8 percent of Indonesian land area but produces more than 50 percent of the rice. Rice is the most strategic staple food in Indonesia. In the future, if most agricultural land is converted to residential and industrial area in the north Java Island, the future of food security in Indonesia may be jeopardized. The findings of the research indicate that to dissuade the farmers from converting their farmland we need to implement programs to improve the agricultural environment and promote a better life in the rural community. The program can prevent the farmlands from being converted to non-agricultural land and maintain food security thus shielding from the impact of the development of the trans-Java toll road.Â Â